Education on invasive mechanical ventilation involving intensive care nurses: a systematic review. Issue 5 (26th March 2018) - Guilhermino, Michelle C; Inder, Kerry J; Sundin, Deborah
ABSTRACT: Background: Intensive care unit nurses are critical for managing mechanical ventilation. Continuing education is essential in building and maintaining nurses' knowledge and skills, potentially improving patient outcomes. Aims: The aim of this study was to determine whether continuing education programmes on invasive mechanical ventilation involving intensive care unit nurses are effective in improving patient outcomes. Methods: Five electronic databases were searched from 2001 to 2016 using keywords such as mechanical ventilation, nursing and education. Inclusion criteria were invasive mechanical ventilation continuing education programmes that involved nurses and measured patient outcomes. Primary outcomes were intensive care unit mortality and in‐hospital mortality. Secondary outcomes included hospital and intensive care unit length of stay, length of intubation, failed weaning trials, re‐intubation incidence, ventilation‐associated pneumonia rate and lung‐protective ventilator strategies. Studies were excluded if they excluded nurses, patients were ventilated for less than 24 h, the education content focused on protocol implementation or oral care exclusively or the outcomes were participant satisfaction. Quality was assessed by two reviewers using an education intervention critical appraisal worksheet and a risk of bias assessment tool. Data were extracted independently by two reviewers and analysed narratively due to heterogeneity. Results: Twelve studies met the inclusion criteria for full review: 11 pre‐ and post‐intervention observational and 1 quasi‐experimental design. Studies reported statistically significant reductions in hospital length of stay, length of intubation, ventilator‐associated pneumonia rates, failed weaning trials and improvements in lung‐protective ventilation compliance. Non‐statistically significant results were reported for in‐hospital and intensive care unit mortality, re‐intubation and intensive care unit length of stay. Conclusion: Limited evidence of the effectiveness of continuing education programmes on mechanical ventilation involving nurses in improving patient outcomes exists. Comprehensive continuing education is required. Relevance to clinical practice: Well‐designed trials are required to confirm that comprehensive continuing education involving intensive care nurses about mechanical ventilation improves patient outcomes.